ANALISIS PENERAPAN EKO-DRAINASE PADA KAWASAN PERUMAHAN GRAND MUSLIM LABUAPI KABUPATEN LOMBOK BARAT - BUDIANTO, MUH BAGUS; SETIAWAN, AGUSTONO; KURNIAWAN, RENDRA NURRAMADHAN (Universitas Mahasaraswati K. Mataram, 2024)
Ecodrainage is a concept for managing rainwater and runoff in urban drainage systems which aims to allow as much water as possible to be absorbed into the ground. During the rainy season, the Grand Muslim Residential area often experiences flooding. One alternative solution is the application of ecodrainage in the form of retention pond and bioretention. This research aims to determine the effectiveness of implementing retention pond and bioretention in reducing the amount of run-off flow. From the results of the analysis it was found that the application of retention ponds could reduce the volume of runoff by 16.25% with a reduction volume of 660 m3 against the incoming flood volume of 4,183.98 m3 originating from Blocks A, B, C, D and E.. Meanwhile the application Bioretention has an efficiency of 1.83% with a reduced discharge of 58.29 lt/sec against the overall housing discharge of 3.193.50 lt/sec.